1998
DOI: 10.1046/j.1365-3113.1998.00060.x
|View full text |Cite
|
Sign up to set email alerts
|

End‐products of behaviour versus behavioural characters: a phylogenetic investigation of pupal cocoon construction and form in some North American black flies (Diptera: Simuliidae)

Abstract: Cocoon spinning was analysed, using video recording and playback, in eighteen Nearctic black fly species, comparing nine Simulium species, six Eusimulium species, Stegopterna mutata, Cnephia dacotensis and Prosimulium mixtum. Fourteen behavioural characters were revealed that produced twenty‐two equally parsimonious trees (CI = 0.93, RI = 0.96). Another tree was constructed on the basis of five characters relating to the cocoon structure (end‐product characters). The goal of the study was to determine whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
3

Year Published

2001
2001
2005
2005

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 17 publications
2
25
0
3
Order By: Relevance
“…A study of the cocoon-spinning behaviour of two simuliine genera with well-formed cocoons (Ectemnia and Simulium), found a suite of shared, derived behavioural character states (synapomorphies) (Stuart & Hunter 1998a). This observation supported the earlier conclusions of Moulton & Adler (1997), who stated explicitly that a well-formed cocoon was a synapomorphy uniting Ectemnia, Metacnephia, and Simulium.…”
Section: Introductionsupporting
confidence: 73%
“…A study of the cocoon-spinning behaviour of two simuliine genera with well-formed cocoons (Ectemnia and Simulium), found a suite of shared, derived behavioural character states (synapomorphies) (Stuart & Hunter 1998a). This observation supported the earlier conclusions of Moulton & Adler (1997), who stated explicitly that a well-formed cocoon was a synapomorphy uniting Ectemnia, Metacnephia, and Simulium.…”
Section: Introductionsupporting
confidence: 73%
“…Thus, unless this detail was missed in observations of the other species ( I can be certain it was not only with W . clara), an apparently homologous structure (multiple vertical sticky lines attached to a suspension line) was built utilizing non-homologou s behaviour (see Hansell, 1984;Eberhard, 1990a;Wenzel, 1992;Stuart and Hunter, 1998 for discussions of the di culties of determining behavioural homologies) .…”
Section: Comparing Webs Of W Sp and Other Wendilgardamentioning
confidence: 99%
“…Wenzel (1993) andde Queiroz andWimberger (1993) have demonstrated that behavioral characters are no more homoplasious than morphological characters, and should be treated as such. Nest architecture and building behavior has been used to investigate the phylogeny of several groups of animals, including spiders (Coddington, 1986;Eberhard, 1982), wasps (Wenzel, 1993), birds (Patterson et al, 1995;Kennedy et al, 1996), fish (McLennan et al, 1988;McLennan, 1993), and black flies (Stuart and Hunter, 1998). In most analyses, the phylogeny as determined by nest architecture and building behavior agrees with those determined by morphology and molecular data.…”
Section: Discussionmentioning
confidence: 89%